Wakaf Uang Beserta Manfaatnya di Tinjau Menurut Perspektif Hukum Islam dan Hukum Perbankan Syariah - Haeratun - (Jatiswara, 2012)
In the modern economic today, money play the important role in determining the community economic activities of a state. Beside function as exchange tool and value standard, money is a main capital for the economic that need not money in funding its development. Based on this expression is got a description on the importance of wakaf in the Muslim communities the role of money in the economic today. However, large potential of zakat is not maximize by the wakaf management. Whereas it has good potential to increase social welfare of Muslim communities, mainly the currency waiaf. Since it strategic for the economic Muslim societies, the currency wakaf should be developed. Fortunately, the legality of the currency wakaf remain debatable in faqih sircle, particularly related to the eternity of the wakaf object. This view basically is not regardless from the logical consequence of zakat as the “sadaqah jariah” with its word flow continually till hereafter.